2019
DOI: 10.1021/acsanm.8b01763
|View full text |Cite
|
Sign up to set email alerts
|

Chemiresistive Sensor Based on Zinc Oxide Nanoflakes for CO2 Detection

Abstract: Ultrafast detection of dynamic variations in the carbon dioxide (CO 2 ) gas concentration with good sensitivity is crucial in many applications that range from respiration monitoring to fire detection. However, the chemical inertness of the CO 2 sensor makes its detection with high sensitivity quite difficult, and only a few materials were reported that can sense CO 2 effectively. Nevertheless, the sensors based on these materials exhibited very low sensitivity with large response times, and thus they are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 42 publications
0
68
0
Order By: Relevance
“…The protocol for device fabrication and sensing experiments were explained in our previous reports [8,9]. MOL2NET, 2019, 5, ISSN: 2624-5078 2 http://sciforum.net/conference/mol2net-05…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for device fabrication and sensing experiments were explained in our previous reports [8,9]. MOL2NET, 2019, 5, ISSN: 2624-5078 2 http://sciforum.net/conference/mol2net-05…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for sensor fabrication and gas sensing experiments were explained in our previous reports [3][4][5].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that the concentration of carbon dioxide in the atmosphere has increased from 310 to 380 ppm in the past half century. [66,67] In many fields, such as submarine technology, aerospace, mining, and rescue operations, it is important to detect the low-concentration of CO 2 in the confined space, [68,69] therefore, it is necessary to continuously detect the low-concentration of CO 2 . [70] The following summarizes the research of MOFs materials as CO 2 capacitive sensors.…”
Section: Application Of Mofs To Co 2 Capacitive Sensingmentioning
confidence: 99%